Verrathene Liebe: Über die vernichtende Wirkung des romantischen Humors in Robert Schumanns Op. 40. - Palsmar, Henrik (Danish Yearbook of Musicology, 2024)
Schumann’s Op. 40 consists of four songs to texts by H. C. Andersen and an anonymous folk song text, all translated into German by Adalbert von Chamisso. Some commentators have felt that the inclusion of the final light and cheerful text disrupted the intended cyclical nature of the work. Based on readings of Jean Paul’s ethical-philosophical concept of romantic humor and Friederich Schlegel’s and Ludwig Tieck’s concept of romantic irony, the article argues that, on the contrary, it is the last song that creates an artistic coherence between the individual songs of the collection. It does this by relativizing, negating or, in the words of Jean Paul and Schlegel, annihilating (vernichten) the content of the others in a romantically humorous way. It is a satirical play that emphasizes and reinforces the seriousness of the others. All five songs tell, in the words of scholar Jon W. Finson, of “grim results of love”, and the title of the last song Verrathene Liebe (Love Betrayed) could be the title of the entire collection.